Reinventing Nilai-Nilai Islam, Budaya, Dan Pancasila Dalam Pengembangan Pendidikan Karakter - Mukhibat, Mukhibat (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2012)
Education is the process of transforming the values in the context of the establishment of private individuals who are able to make sense of themselves, society, and nation. The values that are instilled in the person are extracted from the students’ identity and the identity of the national noble. Cirebon culture is one of cultural treasures owned by the nation. The combination of these two values is a typical characteristic of those found in the body of Cirebon culture. Education that is based on Cirebon culture is not stiff in racing the currents of modernity and the fast, and rapid globalization.